ANALISIS DAMPAK EKONOMI DAN PSIKOLOGI PEMBIAYAAN BAITUL MAAL WAT TAMWIIL (BMT) - Ashfahany, Afief El; Aini, Mei Nurul (I-Economics, 2021)
Baitul Maal Wat Tamwiil (BMT) or Islamic microfinancing has become one of the alternatives for Small and Medium Enterprises (SME’s) problem of financing due to lack of capacity to reach any formal financial institutions such as a bank. This study aims to explore the economic and psychological impact of SMEs by acquiring financial facilities through Islamic microfinancing or BMT. The study is using descriptive with an inductive analysis. This study finds that financing through Islamic microfinance has a positive economic impact to increase the potential income of SMEs. On the other hand, financing through BMT has its positive psychological impact such as peace of mind and increasing the religiosity level of the respondent.